Evaluation of the potential impact of processed foods on public health - Albuquerque, T.G. (2018)
Processed foods are generally recognized as a source of salt, fat and sugar. An excessive intake of these nutrients is perceived as the leading reason for an increased risk in the development of several chronic diseases (obesity, diabetes, cancer and cardiovascular disease). Generally, food processing is associated with negative effects on the quality and safety of foodstuffs. However, food processing is extremely important to extend shelf-life or just to make them edibles. In the last thirty years the processed foods market has grown like never before and every day “new” processed foods with different features are available on the market. Based on the identified priority intervention areas, the aim of this study was to determine salt and total fat contents and fatty acids profile of a selection of processed foods, in order to get an update of the current situation. Between 2014 and 2016, 260 types of processed foods were collected from retail stores, supermarkets, food chains, restaurants and take away in Portugal. Whenever possible, different brands and different retailers for the same type of food were acquired, in order to achieve the best representativeness. The selected food samples were grouped as: cookies, biscuits and wafers (n=61), potato and potato-products (n=47), ready-to-eat meals (n=41), bakery products (n=32), nuts and oilseeds (n=31), fast-food (n=20), snacks (n=13), cereal products (n=11), and sauces (n=4). World Health Organization recommends an intake of salt lower than 5 g/day, in order to prevent cardiovascular diseases. Within the analysed categories of processed foods, the highest contribute is from snacks, for which 100 g can contribute with 95% of the daily intake of salt. Regarding total fat and saturated fatty acids (SFA), the reference intakes are 70 g and 20 g per day, respectively, according to Regulation (EU) n.º 1169/2011. For total fat the food category that contributes with the highest percentage is nuts and oilseeds, while for SFA intake it is the category of potato and potato products followed by snacks. The presented results allow affirming that we are facing a positive trend in relation to the decrease in the levels of total fat for the processed foods under study. However, with respect to the salt and saturated fat content, it was noticed that new challenges will arise for the food industry and policy makers, and the gradual reduction of the aforementioned components, in some of the categories analyzed within the study, should be a priority to promote public health of consumers and to prevent the risk for the development of chronic diseases, namely because some of these foods are highly appreciated by children and young people.